Preliminary report on performance of local and crossbred sheep at Asella Research Station, 1972-1985 - Brannang, E.; Kurtu, M.Y.; Ido, D. (1987)
A preliminary summary of the results of crossbreeding local sheep with Hampshire/Merino. Corriedale and Bleu de Maine rams is presented. Lamb birth weights and weaning weights, and mature ewe body weights all increased with crossbreeding up to the 75% level, but ewe non-pregnancy rates also increased with increasing level of crossbreeding. Maximum productivity in terms of total weight of lamb weaned per ewe bred was achieved at about the 50% level of crossbreeding. The proposed interim breeding policy is to upgrade to about the 50% level with moderately sized exotic breeds having a twinning rate equal to or better tan that of local breeds.